Pengaruh Perbaikan Mutu Proses Terhadap Overall Equipment Effectiveness dan Dampaknya pada Biaya Pokok Produksi - Sugianto, Yogi; Aritonang, MGS.; Kosasih, Kosasih; Kardoko , Hadi (Syntax Corporation, 2025)
The pharmaceutical industry is required to increase efficiency in order to achieve competitive product prices. From the data presented in 2019, the average Overall Equipment Effectiveness (OEE) value at PT Kimia Farma Plant Jakarta is 41%, indicating the low productivity of production machines, where the OEE requirement for world class is 85%. This study aims to analyze the causes of non-ideal OEE values and the impact of process quality improvement on OEE values and cost of production. The type of research used is exploratory descriptive research. Data collection was carried out through secondary data from production records as well as interviews with production operators and supervisors through focus group discussions (FGDs). The results of the study show that the root of the problem of low OEE values is caused by inconsistencies in the implementation of fixed procedures due to operator negligence, lack of supervision, and lack of management commitment to the implementation of preventive maintenance and knowledge management programs. The initial OEE value of 62.67% before the process quality improvement increased to 75.83% after the improvement, indicating an increase of 21%. The average cost of production decreased from IDR 191,368k to IDR 190,255k, a decrease of 0.58%. Process quality improvement has proven to be effective in increasing the effectiveness of production machines and reducing the cost of production.